2014
DOI: 10.1038/bmt.2014.107
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune cytopenias after umbilical cord blood transplantation in adults with hematological malignancies: a single-center experience

Abstract: We describe incidence, clinical features, serological data, response to therapy and outcome of autoimmune cytopenias (ACs), including autoimmune hemolytic anemia (AIHA) and autoimmune thrombocytopenia (AIT) in a series of 281 consecutive adults with hematological malignancies that received single-unit umbilical cord blood transplantation (UCBT) at a single institution. AIHA was diagnosed in 15 patients at a median time of 181 days (range, 25-543), 12 of them had cold antibodies (IgM). The 3-year cumulative inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 25 publications
7
43
4
1
Order By: Relevance
“…Conversely, Sanz et al has reported a 5.4% incidence of AH and 1.4% incidence of ITP in adult single unit CBT recipients at 3 years post-transplant. (REF 11) In contrast to our report, the majority of AH patients in this analysis had cold agglutinins, concomitant viral infections, and chronic GVHD and this complication was associated with a high mortality.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Conversely, Sanz et al has reported a 5.4% incidence of AH and 1.4% incidence of ITP in adult single unit CBT recipients at 3 years post-transplant. (REF 11) In contrast to our report, the majority of AH patients in this analysis had cold agglutinins, concomitant viral infections, and chronic GVHD and this complication was associated with a high mortality.…”
Section: Discussioncontrasting
confidence: 87%
“…However, the literature describing the manifestations of AH and ITP after CBT is limited and the optimal therapy is not established. (REF 7, 8, 9, 10, 11). We performed a retrospective study to characterize the incidence, severity, treatment response, and prognosis of these autoimmune cytopenias in CBT recipients transplanted at our center.…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors of AHDs were mainly associated with source of donors, cGVHD [6, 8], lymphocyte depletion of graft with ex vivo lymphodepletion or in vivo lymphodepletion using ATG or alemtuzumab [7, 13, 22], younger [9] and HLA typing [13] and peripheral blood stem cells, and so on [2]. Our results showed that HRD and cGVHD were the risk factor of AHDs.…”
Section: Discussionmentioning
confidence: 90%
“…4,10,11,16,17,20,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] To our knowledge, our study is the first to describe individual disease courses over time, 11,16,28 transfusion-dependent. Our study is also the first to characterize HRU in CAD, which is substantial in this population.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,31,34,36 Other causes of death included severe anemia complications, 34 ischemic stroke, 40 and infection. 31 In the first year after disease onset, 67% of our cohort used inpatient services at Stanford, 100% used outpatient, and about 50% used emergency services. The median number of CAD-related outpatient visits in the first year after disease onset was 26, representing a significant burden on the patient and the medical system.…”
Section: Discussionmentioning
confidence: 99%